EFEKTIVITAS PENGGUNAAN MEDIA VIDEO YOUTUBE DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VII DI SMPN 3 WARU - Yazidah, Najwa Nur; Mukit, Abd (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
This study aims to determine the effectiveness of the use of YouTube video media on students' learning outcomes in learning Islamic Cultural History. SKI learning is often considered not serious or only as a complement, both by students and educators themselves. This is because SKI material only contains stories and the methods used by educators tend to be monotonous and boring. So that the average learning outcomes obtained are not satisfactory and do not reach the minimum completeness criteria standards. So in this study, the researcher tried to use video media in SKI learning. The research was conducted by providing a pretest and posttest. From the results of the research that has been carried out, there is an increase in student learning outcomes after applying YouTube video media in learning. The average learning outcome before treatment was 69.53 and the learning outcome after treatment was 85.45. In this case, the application of YouTube video media in SKI learning is able to improve student learning outcomes in the medium category.